Board diversity and financial performance: Evidence from Malaysia - Nishanthi, Muthu Chalvan (2023)
This research project unit MKMB25106 Research Project is completed by Nishanthi A/P P. Muthu Chalvan from Master of Business Administration (Corporate Governance) in order to complete my master program. The title of the thesis is “Board Diversity and Financial Performance: Evidence from Malaysia”. The main focus of this research is to identify and synthesize the relationship between board diversity factors and Financial performance. It is also a project that assembles the intellectual interest and critical thinking in solving problems among the postgraduates besides their regular responsibilities. This research project enhances the integration of capabilities and abilities of the postgraduates in the application of theoretical elements into research study. Board diversity is seen as an important element in corporate governance practices as it enhances board performance and productivity level. Increasing board diversity practices at the top level allows to strengthen shareholder’s confidence and provides investors with greater returns. However, studies on board diversity practices appear to be scarce in the Malaysian context; hence, this research is being conducted. The emerging number of studies in various parts of the world has given a chance for the researcher to conduct this study in order to comprehend domestic context. Furthermore, multiple approaches are used to produce the results of this research, and the best technique is chosen to describe the study findings. This will give readers a thorough grasp of the different techniques and applications. On the other hand, the study offers useful recommendations that help future researchers to improve their research quality. This study concludes by providing policymakers, the government, the securities commission, and other relevant parties with recommendations on how to improve board diversity at the board level by enforcing regulations that improve the country's overall image.